Program GENIUS untuk Peningkatan Pengetahuan Ibu Balita tentang MP-ASI dalam Pencegahan Stunting di Kelurahan Bugel, Kota Tangerang - Hikmah, Agnia Nurul; Avindharin, Pundra Dara (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
Background: The reduction of stunting in Indonesia remains lower than that of five other Southeast Asian countries, and the prevalence of stunting in Tangerang City increased in 2023 compared to 2022. This community engagement program aimed to improve mothers’ knowledge of complementary breastfeeding (CBF) guidelines to prevent stunting through an interactive e-module. Methods: The GENIUS program was implemented through educational sessions for mothers of children under five, using an interactive e-module combined with Focus Group Discussions (FGD) at Posyandu Rose and Melati in Bugel Subdistrict, Tangerang City. Results: The proportion of mothers with good knowledge (score >7) increased to 25%, those with moderate knowledge (score 5–7) increased to 47.5%, while mothers with poor knowledge decreased to 27.5%. Conclusion: The GENIUS program effectively improved maternal knowledge, with increases in good and moderate knowledge levels and a reduction in poor knowledge following program implementation.